2013
DOI: 10.1080/17458080.2012.690892
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of structural, electrical and magnetic properties of magnesium ferrite nanoparticles synthesised by sol-gel and co-precipitation techniques

Abstract: A comparative study of structural, electrical and magnetic properties of magnesium ferrite nanoparticles synthesised by sol-gel and co-precipitation techniques, Journal of Experimental Nanoscience, 8:3, 347-357, DOI: 10.1080/17458080.2012 Nano-sized magnesium ferrite was synthesised using co-precipitation and sol-gel techniques. Structural characterisation was performed using X-ray diffractometer (XRD), Fourier transform infrared (FTIR) spectrometer and scanning electron microscope. XRD analysis reveals the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 23 publications
(23 reference statements)
2
6
0
Order By: Relevance
“…These findings are in very good agreement with reports found in the literature [27][28][29] . The results for the magnesium ferrite in turn are in quite-good concordance with ICSD-152468 and with findings previously reported by different groups [30][31][32][33] , presenting peaks located at 2θ ranging from 28 • to 80 • , which are associated with the (220), (311), ( 222), (400), (422), (511), (440), (620) and (533) planes of the MgFe 2 O 4 . For both compositions, the patterns raise fingerprints of phases having cubic symmetry and Fd:3m space group.…”
Section: Methodssupporting
confidence: 91%
“…These findings are in very good agreement with reports found in the literature [27][28][29] . The results for the magnesium ferrite in turn are in quite-good concordance with ICSD-152468 and with findings previously reported by different groups [30][31][32][33] , presenting peaks located at 2θ ranging from 28 • to 80 • , which are associated with the (220), (311), ( 222), (400), (422), (511), (440), (620) and (533) planes of the MgFe 2 O 4 . For both compositions, the patterns raise fingerprints of phases having cubic symmetry and Fd:3m space group.…”
Section: Methodssupporting
confidence: 91%
“…The transmittance spectra of the sample calcined at 150 ∘ C for 24 h are presented in Figure 4. The band observed at 3446 cm −1 is due to the symmetric stretching vibrations of O-H groups and the bands at 1638 and 1121 cm −1 are attributed to the symmetric stretching vibrations of hydrogen-bonded surface water molecules [43], which indicate the absorbed or free water presence in the samples [44]. These vibrations confirm the fact that hydroxyl groups are still reserved in the samples and are not entirely removed even after the samples were calcined at 200 ∘ C [45].…”
Section: Ftir Spectramentioning
confidence: 99%
“…Figures 4(a) and (b) shows, έ and e variation respectively, with frequency for Ni x Cu 1−x Fe 2 O 4 . It was observed that έ increases with the increase of frequency and decreases with the increase of frequency, which may be linked to the conducting networks conceived within the nano-particles and electronic polarization [48][49][50]. According to Koop's theory, the decrease in έ for an increase in frequency can be expressed by considering the solid as composed of well-conducting grains that are separated by poor conducting grain boundaries [51].…”
Section: Dielectric Properties and Em Wave Absorption Propertiesmentioning
confidence: 99%